Generación Automática de Código GUI para IOS para el Grupo de Investigación SINFOCI (2017)
Currently, the software development for mobile devices, specify, for Graphical User Interface (GUI), is make and based on its needs, however, without using patterns or guidelines, it eventually could bring more effort, cost, time and less quality. Every app has a purpose and has many differences with other ones, but, there are common features in all apps, such as usability for success, the relationship between GUI widgets and controller class elements, navigation and interaction between views generated by any event, and the same events what can be used for interface elements. Then, using patterns for GUI code generation under right and well-structured guidelines can give advantage in software development for mobile devices. The main objective of this project is to generate Graphical User Interface (GUI) code (XML), also, Swift code and possibly Objetive-C in interface-related Swift classes for IOS platforms, therefore, to create a well-structured IOS project what can be visible and manipulated by the integrated development environment of Apple, XCode. The above, is generated by five developed models in project management environment Eclipse Modeling Project (EMF, GMF). The generated project can be deployed on IOS emulators or directly on Iphones/Ipads.